An investigation into the introduction of a new wealth tax in South Africa - Arendse, Jacqueline A (Rhodes University, Faculty of Commerce, Department of Accounting, 2018)
In a world of economic uncertainty and manifold social problems, South Africa has its own unique challenges of low economic growth, persistent budget deficits that produce increasing government debt and the highest level of economic inequality in the world. The history of injustice and economic marginalisation and the failure of the economy to provide inclusive growth drives an urgent need to address economic inequality through tax policy, placing ever more focus on wealth taxes as a possible solution. There is a hope is that taxing the wealthy may provide the opportunity to redistribute desperately-needed resources to those denied the opportunity to build wealth and who are trapped in the cycle of poverty. Yet, as appealing as a new wealth tax may seem, the introduction of such a tax carries with it a range of risks, not all of which are known. Of great concern is the possible effect on the economy, which, in its vulnerable state, cannot afford any loss of capital and investment. Very little research has been done on wealth tax in the South African context and there is a dearth of literature focusing on the views and perceptions of the wealthy individuals themselves. This qualitative study investigates the merits and disadvantages of a new wealth tax and seeks to identify any unintended consequences that could result from the implementation of a new wealth tax in South Africa, drawing from historical and international experience and primary data obtained from interviews with individuals likely to be affected by such a tax. Having explored the literature and international experiences with wealth tax and having probed the thinking of wealthy individuals who would be the payers of a wealth tax, the study finds that a new wealth tax may contribute towards the progressivity of the tax system, but it is doubtful whether such a tax would provide a sustainable revenue stream that would be sufficient to address economic inequality and there is a risk of causing harm to the economy. Recognising that the motivation for wealth taxes is often driven more by political argument and public perception than by rational quantitative analysis, the study also anticipates the introduction of a new wealth tax and suggests guidelines for the design of such a tax within the framework for evaluating a good tax system. This study informs the debate on wealth taxes in South Africa and contributes to the design of such a tax, should it be implemented.
Keywords: Wealth tax -- Law and legislation -- South Africa; Taxation -- Law and legislation -- South Africa; Income tax -- South Africa; Fiscal policy -- South Africa; South Africa -- Economic conditions; Income distribution -- South Africa